PENGARUH FIRM SIZE DAN WORLD CONTAINER INDEX TERHADAP KINERJA KEUANGAN SEKTOR LOGISTIK DI ASIA PASIFIK - Maulana Zaenal Muttaqin I M; Ahmad Muslim; Maria C. Widiastuti (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to analyze the effect of firm size and world container index on profitability on logistics companies in Asia and Pacific. Firm size is proxied by total revenue and profitability is measured by return on total assets (ROA) and return on total cost (ROTC). World Container Index (WCI) is measured in units of US Dollars per 40 ft container. This research also explores information related to the profitability of logistics companies in Asia and Pacific during and before the Covid-19 period. The data used in this study is secondary data sourced from the annual report of logistics sector companies available in the TP Catalyst Oriana commercial database for the period 2017-2021. The research sample is selected using the statistical screening method so that 1,959 companies are sampled. Data analysis for hypothesis testing using multiple regression analysis with the Stata program. The results show that firm size and WCI have a significant effect on ROA and ROTC. The research suggests that even during the peak of Covid-19, the logistics sector has a positive financial performance and tends to increase. Keyword : firm size, world container index, ROA, ROTC